Synthesis and antitumor activity of some novel thiophene, pyrimidine, coumarin, pyrazole and pyridine derivatives - Albratty Mohammed; El-Sharkawy Karam Ahmed; Alam Shamsher (Acta Pharmaceutica)
2-Cyano-N-(thiazol-2-yl) acetamide (2a) and 2-cyano-N-(oxazol- 2-yl) acetamide (2b) were obtained via the reaction of ethyl cyanoacetate with either 2-aminothiazole (1a) or 2-aminooxazole (1b). The formed products were directed toward the reaction with cyclopentanone and elemental sulfur in the presence of triethylamine to give cyclopenta[b]thiophene derivatives (3a,b). The latter products were reacted with either ethyl cyanoacetate or malononitrile to form compounds 4a,b and 5a,b, respectively. Compounds 4a,b were aimed at synthesizing some heterocyclic compounds; thus internal cyclization reactions were introduced to form compounds 6a,b. Also, compounds 4a,b reacted with salicylaldehyde, hydrazine derivatives and either urea or thiourea to produce coumarin derivatives (7a,b), pyrazole derivatives (8a-d) and pyrimidine derivatives (9a-d), respectively. Reaction of either benzaldehyde or benzene diazonium chloride (11) with compounds 4a,b afforded compounds 10a,b and 12a,b, respectively. On the other hand, compounds 5a,b underwent internal cyclization to form pyrimidine derivatives 13a,b. Also, when compounds 5a,b reacted with either ethyl cyanoacetate or malononitrile, they gave pyridine derivatives (15a-d) through the formation of intermediates (14a-d). Finally, formation of fused pyrimidine derivatives (17a,b) was achieved through the reaction of compounds 5a,b and salicylaldehyde applying two different pathways. The first pathway used a catalytic amount of piperidine to form compounds 16a,b; the latter products underwent cyclization to give compounds 17a,b. The second pathway, using a catalytic amount of sodium ethoxide solution directly in one step, afforded compounds 17a,b. Structures of the newly synthesized compounds were established using IR, 1H NMR, 13C NMR and mass spectrometry and their antitumor activity was investigated. Some of these compounds showed promising inhibitory effects on three different cell lines. However, fused pyrimidine acetonitrile derivatives 6a and 6b exerted the highest inhibitory effect, comparable to that of doxorubicin.